Nonparametric statistical methods. - Hollander, Myles (John Wiley & Sons, Inc., 2014)
"In this third edition we have improved the eleven chapters of the second edition and added five new chapters. Also organized all of the R programs used in this third edition into a documented collection that is formally registered as an R package specifically linked to this third edition. "--